Chronology of meander abandonment by a large river: a case study based on the São Francisco River, Brazil - Iara Christina de Campos; Rodrigo Wagner Paixão Pinto; Luciana Hiromi Yoshino Kamino; Flávio Fonseca do Carmo; André Augusto Rodrigues Salgado (Revista Brasileira de Geomorfologia)
Meandering rivers are characterized by morphodynamics associated with low energy and high sedimentation rates. Their banks are subject to erosive and depositional processes, which can result in channel migration and the eventual abandonment of meanders. Although this dynamic is known, the time required for events that naturally lead to the abandonment of a meander is still unclear. This work aimed to better understand the temporal dynamics of the abandonment of a large meander from a case study in Volta Grande in Lagoa da Prata/MG, where the São Francisco River underwent artificial straightening in 1981 with the excavation of a 300-m-long channel. For this purpose, images from Landsat 5, Landsat 8 and ResourceSat satellites, captured between 1984 and 2015, were analyzed via false-color band compositions. Although accelerated by human intervention, the process of abandoning the meander occurred slowly and gradually and took more than three decades. This study highlights the complexity and slowness inherent to the natural straightening process in meandering rivers, which involves erosion, sedimentation and adjustment to the new river channel.